PENGARUH INTENSITAS ASET TETAP, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN PAJAK PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2021-2024 - Cyndi Claudia; Theresia Hesti Brawleling (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze and obtain empirical evidence regarding the effect of fixed asset intensity, leverage, and firm size on tax management in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Tax management is an effort undertaken by companies to manage their tax obligations effectively and efficiently in accordance with applicable tax regulations. The independent variables in this study consist of fixed asset intensity, leverage, and firm size, while the dependent variable is tax management, which is proxied by the Effective Tax Rate (ETR). This study employs a quantitative approach with a causal associative research method. The data used are secondary data obtained from the annual financial statements of companies published on the official website of the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in 53 companies with a total of 212 observations. Data analysis was conducted using multiple linear regression with the assistance of Statistical Product and Service Solutions (SPSS) version 25 software. Prior to hypothesis testing, the data were subjected to descriptive statistical analysis and classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that fixed asset intensity has no effect on tax management. Furthermore, leverage and firm size have an effect on tax management. Simultaneously, fixed asset intensity, leverage, and firm size affect tax management.